Outcomes in Patients with Global Pincer Versus Focal Pincer Femoroacetabular Impingement Treated with Hip Arthroscopy: A Retrospective Study with a Minimum 2‐Year Follow‐Up - Jia‐Yi Shao; Zi‐Yi He; Yan Xu; Ling‐Hui Dai; Jian‐quan Wang; Xiao‐Dong Ju (Orthopaedic Surgery, 2023)
Objective Global pincer is a relatively rare form of pincer deformity and is typically associated with technical challenges during surgery. So far, controversy remains whether patients with global pincer have equivalent surgical outcomes compared to patients with focal pincer. This study compares the clinical outcomes of arthroscopic treatment between patients with global pincer femoroacetabular impingement (FAI) and focal pincer FAI in the Chinese population. Methods Data were retrospectively collected from patients with global and focal pincer FAI who underwent hip arthroscopy with a minimum two‐year follow‐up between April 2016 and December 2018. Radiographic measurements, arthroscopic procedures, preoperative and postoperative patient‐reported outcomes (PROs) including modified Harris hip score (mHHS), hip outcome score‐activities of daily living (HOS‐ADL), international hip outcome tool–12 (iHOT‐12), and visual analogue scale (VAS) scores, rates of revision surgery and conversion to total hip arthroplasty (THA) were recorded. Achievement of minimal clinically important difference (MCID) and patient acceptable symptomatic state (PASS) was compared for the VAS, mHHS, HOS‐ADL, and iHOT‐12 scores between groups. Results The total of 33 and 167 patients were included in the global and focal group, respectively. There were no intergroup differences in age, gender, body mass index or follow‐up times. Lateral center‐edge angle (LCEA) was reduced in both groups postoperatively. Both groups demonstrated significant improvements in PROs compared with preoperative levels at the final follow‐up. The preoperative scores showed significant differences in terms of mHHS (60.34 vs 62.90, P = 0.031) and HOS‐ADL (61.45 vs 64.74, P = 0.022) scores between two groups, and the improvement of HOS‐ADL score was significantly higher in global group (P = 0.027). However, the postoperative scores, including VAS, mHHS, HOS‐ADL, and iHOT‐12 scores, showed no significant differences between two groups. And there were no significant differences in the rate of meeting the PASS and MCID between groups. One (3.0%) in the global group and six (3.6%) patients in the focal group underwent revision arthroscopy respectively, with no significant difference (P = 0.876). There were no conversions to THA in both groups. Conclusions Arthroscopic management of global pincer FAI can achieve excellent functional scores at minimum 2‐year follow‐up. The outcomes were similar to focal pincer FAI patients with a low rate of secondary procedure.